2002
DOI: 10.1086/339621
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the β1 Adrenergic Receptor Is Associated with Resting Heart Rate

Abstract: Resting heart rate is significantly associated with cardiovascular morbidity and mortality. However, the extent to which resting heart rate is genetically determined is poorly understood, and no genes have been found that contribute to variation in resting heart rate. Because signaling through the beta1 adrenergic receptor is a key determinant of cardiac function, we tested whether polymorphisms in this receptor are associated with resting heart rate. A cohort of >1,000 individuals of Chinese and Japanese desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
8
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 35 publications
7
119
8
6
Order By: Relevance
“…The Ser49Gly polymorphism, however, did not affect blood pressure (Bengtsson et al 2001a,b). In Caucasians, but not in other ethnicities, this result has been confirmed once ) and contradicted by other investigators (Büscher et al 2001;Ranade et al 2002;O'Shaughnessy et al 2000;Sofowora et al 2003).…”
Section: Genetic Variants In β-Adrenoceptor Genesmentioning
confidence: 76%
“…The Ser49Gly polymorphism, however, did not affect blood pressure (Bengtsson et al 2001a,b). In Caucasians, but not in other ethnicities, this result has been confirmed once ) and contradicted by other investigators (Büscher et al 2001;Ranade et al 2002;O'Shaughnessy et al 2000;Sofowora et al 2003).…”
Section: Genetic Variants In β-Adrenoceptor Genesmentioning
confidence: 76%
“…In addition, our findings are largely consistent with the literature in that b 1 -AR codon 389 genotype does not appear to influence HR response to b-receptor agonists, antagonists or exercise, nor does it appear to affect resting HR. [4][5][6][18][19][20][21] Taken together, these data in myriad patient populations suggest that while the functional effects of the b 1 -AR codon 389 polymorphism have been documented in numerous settings, it seems now it may be clearly concluded that this polymorphism does not affect HR, or its responses to agonists, antagonists or exercise.…”
Section: Discussionmentioning
confidence: 98%
“…[13][14][15] Several functional analyses have addressed these SNPs; for example, participants with the Gly allele in the Ser49Gly polymorphism of b 1 ADR have been reported to have a lower heart rate. 16 In vitro studies of isoproterenol stimulation showed that Arg389 in b 1 ADR produces higher levels of adenylyl cyclase activity, resulting in enhanced cardiac sensitivity to catecholamines. 17 The Gly16 and Glu27 polymorphisms in b 2 ADR have been associated with sympathetic overactivity, as reflected by high plasma norepinephrine levels.…”
Section: Discussionmentioning
confidence: 99%